The Influence of Artificial Intelligence in the Performance of Production Planning for Industrial Motors - Tokarev, Mikhail; Martínez, Felipe; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
With artificial intelligence becoming more widespread in business, this thesis explores the usage of AI in production planning. The aim being to examine the impact AI would have on the production planning of industrial motors, mainly the accuracy, efficiency, and adaptability to fluctuations. Additionally, this thesis will objectively examine the challenges and shortcomings of the implementation of artificial intelligence for production planning, showcasing the potential drawbacks that businesses should consider before choosing to implement AI in their production planning process. With motors typically requiring high customizability and precision to fit the customer needs, the production planning process must properly account for this.
Vedoucí práce: Felipe Martínez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses